Forecasting technique using time sequence: model penentuan volume produksi Sanjai di UKM Rina Payakumbuh - Marlina, Winny Alna; Susiana, Susiana; N, Erizal; Ahmad, Faisal Ali (Jurnal Manajemen, 2018)
Forecasting is essential for factories to gain competitive ad-vantages. Forecasting is estimates of values at certain specific future times. Forecasting helps in reducing inventory and to schedule customers’ orders. Accurate sales forecasting is very helpful in planning of plant procurement and for cutting the cost. Sanjai Rina on Payakumbuh is a small business who sell traditional food with-out using forecasting method. In this case inventory of traditional food was affected to out of stock or over stocked. In this paper, forecasting methods using time series such linear method, exponential smoothing, etc. Forecasting based on historical data then the suggestion forecasting model will be implemented to this business. Using standard estimation error (SEE) to estimate the error of fore-casting. The result show that exponential methods were more accurate concrete to other. With exponential methods, Sanjai demand for next period can be estimated on ward become more effective and efficient. Peramalan sangat penting bagi pabrik untuk mendapatkan keunggulan kompetitif. Peramalan adalah perkiraan nilai pada waktu mendatang tertentu. Peramalan membantu dalam mengurangi persediaan dan untuk menjadwalkan pesanan pelanggan. Perkiraan penjualan yang akurat sangat membantu dalam perencanaan pengadaan pabrik dan untuk memotong biaya. Sanjai Rina di Payakumbuh adalah usaha kecil yang menjual makanan tradisional tanpa menggunakan metode peramalan. Dalam hal ini persediaan makanan tradisional dipengaruhi kehabisan stok atau kelebihan persediaan. Dalam tulisan ini, metode peramalan menggunakan deret waktu seperti metode linear, perataan eksponensial, dll. Peramalan berdasarkan data historis maka model peramalan saran akan diterapkan pada bisnis ini. Menggunakan standard error estimasi (SEE) untuk memperkirakan kesalahan forecasting. Hasil penelitian menunjukkan bahwa metode eksponensial lebih konkret tingkat ke yang lain. Dengan metode eksponensial, permintaan Sanjai untuk periode selanjutnya dapat diperkirakan lingkungan menjadi lebih efektif dan efisien.